Profile of the Patient Who Refuses to Participate in the Expert Patients Program. (June 2014) - Vega, Gema; Vega, Maria; Alajarín, Llanos I.; Portero, Begoña; Ruíz, Teresa; Ruiz, Victoria; Marín, Conception; Lázaro, Conception; Gómez, Mercedes; Conde, Fernando
The Expert Patients Program (EPP), an educational intervention for chronic diseases aimed at nonprofessionals, has high nonparticipation and dropout rates. We used quantitative and qualitative methods to identify the prevalence of and reasons for nonparticipation in 100 patients with acute myocardial infarction and 69 with stroke. We confirmed a high prevalence of refusal, identifying three groups based on degree of participation: patients who refused to attend (51%), patients who attended and then dropped out (10%), and patients who attended (39%). Patients who refused to participate or dropped out were mainly women and former/current smokers with a better-than-average physical condition. In addition, they were invited to participate in the EPP long after their cardiovascular event. We found that the degree of participation depended upon the patient's individual and social context and the professional profile of the recruiter. Therefore, tailored strategic interventions should be designed for each type of participation.